2018
DOI: 10.1111/cea.13305
|View full text |Cite
|
Sign up to set email alerts
|

Blocking antibodies induced by peanut oral and sublingual immunotherapy suppress basophil activation and are associated with sustained unresponsiveness

Abstract: Background: Oral and sublingual immunotherapies for peanut allergy have demonstrated efficacy in small clinical trials; however, mechanisms and biomarkers correlating with clinical outcomes remain elusive. Previous studies have demonstrated a role for IgG in post-OIT plasma in the suppression of IgE-mediated mast cell reactions. Objective: The aim of this study was to characterize the role that peanut oral and sublingual immunotherapy-induced plasma factors play in the inhibition of ex vivo basophil activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 28 publications
1
36
1
1
Order By: Relevance
“…Depletion of IgG, specifically IgG 4 , has been shown to eliminate the inhibitory effect of OIT plasma in basophil activation. 28,40,44 We did not find direct associations between peanut-induced % CD63 high basophils and levels of peanut sIgG 4 alone; however, we detected significant but weak correlations between peanut-induced %CD63 high basophils and sIgG 4 /sIgE before and after OIT, as well as a moderate correlation between peanut-induced %CD63 high basophils and sIgE/total IgE after OIT. These findings suggest that basophil activation is regulated by the summation of activating (such as sIgE) and inhibitory (eg, IgG 1 and IgG 4 ) immunoglobulins.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Depletion of IgG, specifically IgG 4 , has been shown to eliminate the inhibitory effect of OIT plasma in basophil activation. 28,40,44 We did not find direct associations between peanut-induced % CD63 high basophils and levels of peanut sIgG 4 alone; however, we detected significant but weak correlations between peanut-induced %CD63 high basophils and sIgG 4 /sIgE before and after OIT, as well as a moderate correlation between peanut-induced %CD63 high basophils and sIgE/total IgE after OIT. These findings suggest that basophil activation is regulated by the summation of activating (such as sIgE) and inhibitory (eg, IgG 1 and IgG 4 ) immunoglobulins.…”
Section: Discussioncontrasting
confidence: 75%
“…21,22 Some studies have suggested that BATs are more reliable than skin prick tests and sIgE levels in differentiating food allergy from tolerance in children. 32,34 Although suppression of basophil activation by immunotherapy has been demonstrated in food allergy to egg, 37 milk, 38 and peanut, 7,8,18,[25][26][27]39,40 only a few studies have examined the association of basophil activation with treatment outcomes. 18,26,27,37,40,41 Our analysis of BAT results obtained for more than 2 years in the POISED study shows that basophil activation remains suppressed even after 13 weeks off active OIT, and that sustained protection is associated with lower levels of basophil activation by peanut before, during, and after OIT.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the induction of blocking antibodies with POIT, as previously reported by us 2 and others, 6,7 and demonstrate, for the first time, that POIT did not change the functional characteristics of IgE, as determined by the ability of effector cells, such as mast cells and basophils, to respond to peanut allergens with cellular activation, degranulation, mediator release, and consequent acute allergic reactions to peanut. The enhanced mast cell response to anti-IgE after POIT suggests that continued exposure to the allergen can potentiate IgE-mediated mast cell responses.…”
Section: Peanut Oral Immunotherapy Induces Blocking Antibodies But Dosupporting
confidence: 92%
“…Toll-like receptors. 7 These findings suggest that TNF, together with other innate cytokines, including IL-33, might play a role in protection from helminth infection through activation of ILC2s.…”
mentioning
confidence: 90%
“…Orgel et al have investigated the mechanisms of action of oral immunotherapy (OIT) for peanut allergy . We know that specific IgG levels increase post‐OIT but whether this underlies the clinical impact of OIT is unclear.…”
mentioning
confidence: 99%